PENILAIAN PRODUK KANCING BERBENTUK HURUF DENGAN BAHAN DASAR LIMBAH STYROFOAM - Fiqratul Aulia, Fika; Lutfia Zahra, Eneng; Suliyanthini, Dewi (Universitas Negeri Jakarta, 2021)
The research aims to find out the assessment of Styrofoam Letter-Shaped Button Products full colour theme, Rainbow inspiration source, style and look sporty off beat which is assessed based on product quality theory and design element theory and design principles. Descriptive qualitative research methods. By measuring based on aspects of comfort, benefits, the shape of the center of attention color and the element of design. Valued by 5 panelists. The results of the button accessories research has a design element of color shape texture was quite good. And can be used as a button for children's clothing. But in performance it takes a more perfect improvement process.